2003
DOI: 10.1016/j.worlddev.2003.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Research-Led Agricultural Productivity Growth on Poverty Reduction in Africa, Asia and Latin America

Abstract: Twenty percent of the world population, or 1.2 billion live on less than $1 per day; 70% of these are rural and 90% in Asia and Sub-Saharan Africa. Research led technological change in agriculture generates sufficient productivity growth to give high rates of return in Africa and Asia and has a substantial impact on poverty, currently reducing this number by 27 million per annum, whereas productivity growth in industry and services has no impact. The per capita "cost" of poverty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
275
3
15

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(305 citation statements)
references
References 17 publications
12
275
3
15
Order By: Relevance
“…6), as can enhanced biotechnological (43) inputs. Recent research has suggested that investments in African agricultural development will lead to substantial propoor economic growth (43)(44)(45). Our analysis suggests that the continuation of recent tendencies will be likely to result in continued increases in undernourishment; but this is not a fait accompli.…”
Section: Discussionmentioning
confidence: 68%
“…6), as can enhanced biotechnological (43) inputs. Recent research has suggested that investments in African agricultural development will lead to substantial propoor economic growth (43)(44)(45). Our analysis suggests that the continuation of recent tendencies will be likely to result in continued increases in undernourishment; but this is not a fait accompli.…”
Section: Discussionmentioning
confidence: 68%
“…These studies generally find high poverty reduction elasticities for agricultural productivity growth (2). In Asia, it has been estimated that each 1% increase in crop productivity reduces the number of poor people by 0.48% (38). In India, it is estimated that a 1% increase in agricultural value added per hectare leads to a 0.4% reduction in poverty in the short run and 1.9% reduction in the long run, the latter arising through the indirect effects of lower food prices and higher wages (39).…”
Section: Limitations Of Gr-led Growth Strategiesmentioning
confidence: 99%
“…(Pinstrup-Andersen & Hazell, 1987, p. 1). Other researchers also affirm this; among them are Hazell (2009);Rosegrant and Hazell (2000); Hazell and Haddad (2001); Lipton and Longhurst (1989); Thirtle et al (2003); Ravallion and Datt (1996);and Fan et al (2000). This policy push is premised on the fact that, " […] no Asian country developed its food staple agriculture from subsistence to market orientation without public intervention [....]" (Diao et al, 2007, p. 18).…”
Section: Conclusion: Food Security Vision For Ssamentioning
confidence: 99%